Investigation of Peak Particle Velocity Variations during Impact Pile Driving Process - Maryam Rezaei; Amir Hamidi; Abtin Farshi Homayoun Rooz (Civil Engineering Infrastructures Journal, 2016)
Impact pile driving is a multi-component problem which is associated to multi-directional ground vibrations. At first, vibration is transferred from the hammer to the pile and then to the common interface of pile and soil. This is then transferred to the environment and has great impact on the adjacent structures, causing disturbance to residents and also damage to the buildings. It is of high importance to have sufficient estimation of pile driving vibration level in order to maintain the comfort of residents near the site and also to prevent the structural damage to buildings. In this study, a finite element model, using ABAQUS, with the ability of simulating continuous pile driving process from the ground surface, was introduced. The model was verified by comparing the computed peak particle velocities with those measured in the field. Parameters affecting the peak particle velocity (PPV), for example elastic modulus, shear strength parameters, impact force, pile diameter, etc. were considered, and variations of PPV was investigated. Results of present study indicated that PPV at the ground surface does not occur when the pile toe is located on the ground surface; as the pile penetrates into the ground, PPV reaches a maximum value at a critical depth of penetration. Moreover, the amplitude of vibration on the ground surface reduced logarithmically with increasing distance to the pile. Also, on the ground surface and radial distances of 3 to 20 m, maximum particle velocity occurred between 1 to 5 m depths of pile penetration. The results showed PPV as being directly proportional to the hammer impact force, pile diameter, friction angle and cohesion intercept and inversely proportional to the elastic modulus of the soil.